2014
DOI: 10.1007/s40618-014-0165-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-neutralizing CYP24A1 expression, oncogenic mutation states and histological findings of human papillary thyroid cancer

Abstract: A definite alteration was seen in vitamin D3-inactivating CYP24A1 gene activity in PTC compared to their normal tissues on a relatively large patient population. Our findings raise the possibility that CYP24A1 may also directly be involved in thyroid carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
1
19
0
3
Order By: Relevance
“…The association between enhanced CYP24A1 activity and tumorigenesis has been previously reported ( 8 ). Following transfection with CYP24A1 siRNA, CYP24A1 expression was significantly downregulated ( Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The association between enhanced CYP24A1 activity and tumorigenesis has been previously reported ( 8 ). Following transfection with CYP24A1 siRNA, CYP24A1 expression was significantly downregulated ( Fig.…”
Section: Resultssupporting
confidence: 57%
“…The primary effect of 1,25-D3 is to regulate bone and calcium homeostasis. However, this active form of vitamin D3 also exhibits non-classical effects, including regulation of the cell cycle and various anti-tumor effects, and is therefore attracting increased attention ( 6 8 ). It has been demonstrated that 1,25-D3 is implicated in various types of cancer ( 9 – 11 ), including thyroid cancer, where its concentration was reduced ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…PCR in tissue specimens of 60 patients (Zou et al 2014). The same was corroborated by Balla and co-workers who examined CYP24A1 expression by real-time quantitative PCR in normal and cancer tissue sections of 100 patients with PTC: tumor malignity variables (i. e., vascular invasion, lymph node involvement, tumor size, and hypothyreosis) correlated with CYP24A1 expression(Balla et al 2014). Resistance to calcitriol (and another VDR agonist) was observed in cells with high baseline…”
mentioning
confidence: 52%
“…19 Similarly, others have shown that CYP24A1 is preferentially expressed to a greater degree in thyroid cancers with other somatic oncogenic mutations. 21 These data Figure 5. Complex relationship between cytochrome P450 family 24 subfamily A member 1 (CYP24A1) and KRAS.…”
Section: Discussionmentioning
confidence: 91%